Na+/K+-ATPase and lipid peroxidation in forebrain cortex and hippocampus of sleep-deprived rats treated with therapeutic lithium concentration for different periods of time - Vosahlikova, Miroslava; Roubalova, Lenka; Cechova, Kristina; Kaufman, Jonas; Musil, Stanislav; Miksik, Ivan; Alda, Martin; Svoboda, Petr (Progress in neuro-psychopharmacology & biological psychiatry, 2020)
Lithium (Li) is a typical mood stabilizer and the first choice for treatment of bipolar disorder (BD). Despite an extensive clinical use of Li, its mechanisms of action remain widely different and debated. In this work, we studied the time-course of the therapeutic Li effects on ouabain-sensitive Na+/K+-ATPase in forebrain cortex and hippocampus of rats exposed to 3-day sleep deprivation (SD). We also monitored lipid peroxidation as malondialdehyde (MDA) production. In samples of plasma collected from all experimental groups of animals, Li concentrations were followed by ICP-MS. The acute (1 day), short-term (7 days) and chronic (28 days) treatment of rats with Li resulted in large decrease of Na+/K+-ATPase activity in both brain parts. At the same time, SD of control, Li-untreated rats increased Na+/K+-ATPase along with increased production of MDA. The SD-induced increase of Na+/K+-ATPase and MDA was attenuated in Li-treated rats. While SD results in a positive change of Na+/K+-ATPase, the inhibitory effect of Li treatment may be interpreted as a pharmacological mechanism causing a normalization of the stress-induced shift and return the Na+/K+-ATPase back to control level. We conclude that SD alone up-regulates Na+/K+-ATPase together with increased peroxidative damage of lipids. Chronic treatment of rats with Li before SD, protects the brain tissue against this type of damage and decreases Na+/K+-ATPase level back to control level.
Keywords: Animals; Antimanic Agents; Rats; Sodium-Potassium-Exchanging ATPase; hipokampus; Rats, Wistar; Lithium Carbonate; antimanika; Lipid peroxidation; spánková deprivace; Prosencephalon; přední mozek; Binding, Competitive; Lithium; Ouabain; peroxidace lipidů; Sleep deprivation; Lipid Peroxidation; ouabain; Rat brain; Male; kompetitivní vazba; Malondialdehyde; Sleep Deprivation; krysa rodu Rattus; lithiumkarbonát; Hippocampus; malondialdehyd; zvířata; mužské pohlaví; sodíko-draslíková ATPasa; Na(+)/K(+)-ATPase; potkani Wistar